Novel Asaia bogorensis Signal Sequences for Plasmodium Inhibition in Anopheles stephensi - Grogan, Christina; Bennett, Marissa; Moore, Shannon; Lampe, David (Frontiers in Microbiology, 2021)
Mosquitoes vector many pathogens that cause human disease, such as malaria that is caused by parasites in the genus Plasmodium. Current strategies to control vector-transmitted diseases are hindered by mosquito and pathogen resistance, so research has turned to altering the microbiota of the vectors. In this strategy, called paratransgenesis, symbiotic bacteria are genetically modified to affect the mosquito’s phenotype by engineering them to deliver antiplasmodial effector molecules into the midgut to kill parasites. One paratransgenesis candidate is Asaia bogorensis, a Gram-negative, rod-shaped bacterium colonizing the midgut, ovaries, and salivary glands of Anopheles sp. mosquitoes. However, common secretion signals from E. coli and closely related species do not function in Asaia. Here, we report evaluation of 20 native Asaia N-terminal signal sequences predicted from bioinformatics for their ability to mediate increased levels of antiplasmodial effector molecules directed to the periplasm and ultimately outside the cell. We tested the hypothesis that by increasing the amount of antiplasmodials released from the cell we would also increase parasite killing power. We scanned the Asaia bogorensis SF2.1 genome to identify signal sequences from extra-cytoplasmic proteins and fused these to the reporter protein alkaline phosphatase. Six signals resulted in significant levels of protein released from the Asaia bacterium. Three signals were successfully used to drive the release of the antimicrobial peptide, scorpine. Further testing in mosquitoes demonstrated that these three Asaia strains were able to suppress the number of oocysts formed after a blood meal containing P. berghei to a significantly greater degree than wild-type Asaia, although prevalence was not decreased beyond levels obtained with a previously isolated siderophore receptor signal sequence. We interpret these results to indicate that there is a maximum level of suppression that can be achieved when the effectors are constitutively driven due to stress on the symbionts. This suggests that simply increasing the amount of antiplasmodial effector molecules in the midgut is insufficient to create superior paratransgenic bacterial strains and that symbiont fitness must be considered as well.